2017
DOI: 10.1007/s10826-017-0737-1
|View full text |Cite
|
Sign up to set email alerts
|

Couple Conflict in Parents of Children with versus without Autism: Self-Reported and Observed Findings

Abstract: We compared the couple conflict of parents of children with autism spectrum disorder (ASD) to a comparison group of parents of children without disabilities using self-reported and observational measures. In total, 178 couples who had a child with ASD (aged 5–12 years) and 174 couples who had children without disabilities (aged 5–12 years), recruited from a Midwestern state in the United States, reported on couple conflict in everyday life and engaged in an observed couple conflict interaction. Parents of chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 53 publications
1
39
1
Order By: Relevance
“…Research shows that raising a child with ASD may increase marital conflicts (i.e., confrontations, arguments, and disputes in marriage) and reduce marital love (i.e., spousal feelings of passion, intimacy, and commitment) among parents [Sim, Cordier, Vaz, & Falkmer, 2016]. Cross-sectional, correlational studies, for example, have shown that, compared to parents of typically developing children and parents of children with other developmental disabilities, parents of children with ASD report lower levels of marital adjustment, satisfaction, and happiness and higher levels of marital separation, divorce, and dissolution [Gau et al, 2012;Hartley, Papp, et al, 2017;Hartley et al, 2010;Lee, 2009]. Longitudinal studies have further demonstrated that spousal perceptions of marital connectedness, closeness, and attachment often decline after the birth of a child with ASD [Hartley, Barker, Baker, Seltzer, & Greenberg, 2012].…”
Section: Child Autistic Symptoms and Parental Marital Qualitiesmentioning
confidence: 99%
“…Research shows that raising a child with ASD may increase marital conflicts (i.e., confrontations, arguments, and disputes in marriage) and reduce marital love (i.e., spousal feelings of passion, intimacy, and commitment) among parents [Sim, Cordier, Vaz, & Falkmer, 2016]. Cross-sectional, correlational studies, for example, have shown that, compared to parents of typically developing children and parents of children with other developmental disabilities, parents of children with ASD report lower levels of marital adjustment, satisfaction, and happiness and higher levels of marital separation, divorce, and dissolution [Gau et al, 2012;Hartley, Papp, et al, 2017;Hartley et al, 2010;Lee, 2009]. Longitudinal studies have further demonstrated that spousal perceptions of marital connectedness, closeness, and attachment often decline after the birth of a child with ASD [Hartley, Barker, Baker, Seltzer, & Greenberg, 2012].…”
Section: Child Autistic Symptoms and Parental Marital Qualitiesmentioning
confidence: 99%
“…According to previous studies, caring for special needs children causes many problems among parents on ordinary days; however, parents with special needs children experience more physical, social, and emotional challenges compared to parents of typically developing children [ 5 ]. They also face a greater risk of psychological burden and experience various mental health problems such as anxiety [ 4 , 6 ], depression [ 3 ], marital discord [ 7 ], and sleep problems [ 8 ]. Parents with differently challenged special needs children may display diverse types of mental health problems; however, anxiety and depression are the most common [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In non-ASD populations, high parenting stress and poor parental psychological well-being is associated with distant and critical parent-child interactions (Mackler et al, 2015). As a group, parents of children with ASD also report less satisfying parent couple relationships (Sim et al, 2016) and more couple conflicts (Hartley et al, 2017), and are at greater risk for separation/divorce (Baeza-Velasco, Michelon, Rattaz, Pernon, & Baghdadli, 2013;Hartley et al, 2010) than parents of children without ASD. Thus, parents of children with ASD may also be at risk for negative emotional quality parent couple relationships.…”
Section: Introduction Emotional Quality Of Family Subsystems and Asdmentioning
confidence: 99%
“…There are no published FMSS studies of parent couple relationship quality in families of children with ASD. Given their group-level risk for unsatisfying, conflict-ridden, and shorter-term couple relationships (Sim et al, 2016;Hartley et al, 2010;Hartley et al, 2017), many families of children with ASD may consist of one or both parents expressing low warmth and high criticism toward her/his partner.…”
Section: Introduction Emotional Quality Of Family Subsystems and Asdmentioning
confidence: 99%